2012
DOI: 10.1002/mds.24947
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology of psychogenic movement disorders in children

Abstract: Psychogenic movement disorders are heterogeneous and diagnostically challenging. Despite the growing literature on adult forms, clinical features in children have received relatively little attention. We retrospectively reviewed medical records and video of patients <18 years diagnosed with a psychogenic movement disorder at our institute between 2007 and 2010. We identified 14 patients (6 males and 8 females) with a mean onset age of 11.5 years. Levels of diagnostic confidence were documented (2 patients), cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…In a large cohort of 54 children with PMD, Ferrara and Jankovic reported tremor as the most common movement disorder (65%), followed by dystonia, myoclonus, and gait abnormality . Canavese and colleagues reported that tremor (36%) was the most common PMD phenotype in 14 children . Fernandez‐Alvarez also reported 16 children with PMD and observed that tremor (68%) was the predominant movement disorder, followed by myoclonus .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a large cohort of 54 children with PMD, Ferrara and Jankovic reported tremor as the most common movement disorder (65%), followed by dystonia, myoclonus, and gait abnormality . Canavese and colleagues reported that tremor (36%) was the most common PMD phenotype in 14 children . Fernandez‐Alvarez also reported 16 children with PMD and observed that tremor (68%) was the predominant movement disorder, followed by myoclonus .…”
Section: Discussionmentioning
confidence: 97%
“…Limited data are available on PMD in children, and most of the existing literature relates only to adults . Therefore, we undertook this retrospective study of 33 adults and 25 children who were diagnosed with PMD to delineate their clinical characteristics, risk factors, and outcomes.…”
mentioning
confidence: 99%
“…FMD usually presents as a single movement disorder affecting the dominant extremities, however, complex movements or gait disorders are also common [26][27][28]. Children with functional disorders are expected to make a full recovery, as the conversion symptoms last no longer than 3 months typically [29].…”
Section: Clinical Spectrummentioning
confidence: 99%
“…The most common motor presentations are tremor, dystonia, gait disorders and myoclonus,17 23 24 but parkinsonism, chorea and tics have also been reported 23. Psychogenic paroxysmal movements have been described and differential diagnosis with PNKD could constitute a diagnostic challenge 25…”
Section: Introductionmentioning
confidence: 99%